Effect of music on preoperative anxiety and postoperative pain in patients undergoing gynecological surgery: A meta-analysis - Li Yang; Yong Lin; Yan Long (PLoS ONE, 2025)
Background Preoperative anxiety and postoperative pain often afflict patients and may impact surgical safety and postoperative recovery. Therefore, we studied the influence of music for patients with preoperative anxiety and postoperative pain, in order to provide an effective and safe non-pharmacological intervention for patients. Method Studies on music and gynecological operation were searched in PubMed, EMBASE, Web of Science, and the Cochrane Library. NOS and the modified Jadad Scale were used to evaluate the quality of the studies, and the evidence quality was evaluated and graded according to GRADE guidelines. Stata 12.0 software was used for data analysis. Results We compared the difference in preoperative anxiety between the experimental group and the control group. The results showed that anxiety symptoms were significantly relieved in the experimental group that listened to music(WMD = -6.78, 95% CI (-7.54 - -6.03), P = 0.000). This difference was statistically significant, and the quality of evidence was rated as intermediate. We compared the difference in anxiety symptoms before and after listening to music in the experimental group (WMD = -4.39, 95% CI (-5.14 - -3.64), P = 0.000). The results indicated a significant relief in anxiety symptoms after listening to music. The difference was statistically significant, and the quality of evidence was rated as intermediate and low, respectively. We compared the differences in postoperative pain between the experimental group and the control group (WMD = -0.26, 95% CI (-0.43–-0.10), P = 0.002). The results showed that the pain symptoms of the experimental group, who listened to music, were significantly relieved. The difference was statistically significant, and the quality of evidence was rated as intermediate. Conclusion This meta-analysis showed that listening to music significantly improved preoperative anxiety and postoperative pain during gynecological surgery. Therefore, operating room nurses should perform music intervention in patients undergoing gynecological surgery before and after surgery.